2014
DOI: 10.1074/jbc.m114.566927
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Phosphoenolpyruvate Carboxykinase (PEPCK-M) Is a Pro-survival, Endoplasmic Reticulum (ER) Stress Response Gene Involved in Tumor Cell Adaptation to Nutrient Availability

Abstract: Background:The integrated stress response (ISR) is necessary to help the tumor adapt to its microenvironment. Results: ATF4 activates a PEPCK-M-dependent pro-survival pathway under amino acid deprivation or ER stress (ISR) by binding to its proximal promoter. Conclusion: PEPCK-M participates in supportive adaptations of cancer cells under stress. Significance: A previously unappreciated role for PEPCK-M in cancer cells opens a therapeutic window and enhances our understanding of cancer metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
143
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(156 citation statements)
references
References 48 publications
10
143
0
3
Order By: Relevance
“…7F). These data are consistent with recent reports that glucose deprivation results in an increase in Pck expression (33, 34) which promotes metabolic flexibility when nutrients are limiting (35,36). Also, these data show the utility of assessing a phenotype across a series of genetic perturbations.…”
Section: Mpc Deficiency Promotes Metabolic Plasticity In Uterosupporting
confidence: 81%
“…7F). These data are consistent with recent reports that glucose deprivation results in an increase in Pck expression (33, 34) which promotes metabolic flexibility when nutrients are limiting (35,36). Also, these data show the utility of assessing a phenotype across a series of genetic perturbations.…”
Section: Mpc Deficiency Promotes Metabolic Plasticity In Uterosupporting
confidence: 81%
“…We further demonstrated that PCK2 limits cancer cell death under low glucose conditions and in 3D spheroids (3). Similar findings on PCK2 were obtained in breast, cervical, and colon carcinoma cells and published this year as well (4 …”
supporting
confidence: 71%
“…Posteriormente Qu et al (2016), informaron que el estrés calórico induce la expresión de la enzima fosfoenolpiruvato carboxiquinasa (PEPCK-C) en el tejido adiposo, provocando una elevación en la gliceroneogénesis, lo que podría explicar el aumento de la acumulación de grasa en los cerdos criados en ambiente con temperaturas elevadas. La fosfoenolpiruvato carboxiquinasa (PEPCK) se encuentra en dos isoformas (PEPCK-C y PEPCK-M); la PEPCKC se expresa principalmente en el hígado, el riñón y el tejido adiposo; en tanto que la PEPCK-M está presente en una variedad de tejidos no gluconeogénicos, incluyendo páncreas, cerebro, leucocitos, corazón o neuronas (Méndez-Lucas et al, 2014). En un estudio previo Méndez-Lucas et al (2013) concluyeron que la PEPCK-M tiene potencial gluconeogénico per se y coopera con la PEPCK-C para ajustar el flujo gluconeogénico a los cambios en la disponibilidad de sustrato o energía en el ciclo de Krebs, sugiriendo un papel en la regulación del metabolismo de glucosa y lípidos en el hígado.…”
Section: Resultados Y Discusiónunclassified
“…En un estudio previo Méndez-Lucas et al (2013) concluyeron que la PEPCK-M tiene potencial gluconeogénico per se y coopera con la PEPCK-C para ajustar el flujo gluconeogénico a los cambios en la disponibilidad de sustrato o energía en el ciclo de Krebs, sugiriendo un papel en la regulación del metabolismo de glucosa y lípidos en el hígado. Méndez-Lucas et al (2014) sugirieron que la PEPCK-M es importante para mantener la progresión y sobrevivencia celular bajo condiciones de estrés. Los resultados obtenidos en el presente estudio, sugieren que el mayor EGD observado en las cerdas que consumieron alimento adicionado con Met-Zn durante la época de calor, pudo estar influenciado por el Zn, mejorando la actividad enzimática en la síntesis y deposición de tejido adiposo.…”
Section: Resultados Y Discusiónunclassified